Effects of indigenous microorganism and system of rice intensification formulation on growth, physiology, nutrient uptake and rice yield - Sakimin, Siti Zaharah; Abd Rahim, Nur Azwani; Juraimi, Abdul Shukor; Alam, Md Amirul; Aslani, Farzad (Bangladesh Botanical Society, 2017)
The application of indigenous microorganism (IMO) and system of rice intensification (SRI) Anak formulation on growth and nutrient uptake of rice variety MR219 at nursery level was carried out. Results showed the highest plant height, leaf area, fresh and dry weight of rice variety MR219 when treated with IMO and SRI Anak formulation. Accumulation of N, P and K content in leaf and root tissue is much affected by spraying with SRI formulation. IMO had less influence in increasing the nutrient content in leaf and root tissue at nursery level. IMO and SRI formulation is potentially to be used as bio-fertilizer and bio-regulator to reduce environmental problems.